Project a black planet the art and culture of Panafrica - Byrd, Antawan I.; Dyangani Ose, Elvira 1974-; Getachew, Adom ca. 20./21. Jh; Witkovsky, Matthew S. 1967- (Art Institute of Chicago, 2024)
"An expansive look at more than a century of Pan-Africanist art and the ways it embodies the movement’s principles and global ambitions. Since the term Pan-Africanism was coined around 1900, the movement’s promise has been to foster liberation and solidarity for Black peoples worldwide. Focusing on its cultural expression, this book presents a rich selection of the visual, sonic, and other creative forms that have emerged throughout Pan-Africanism’s evolution. Among the nearly two hundred artists represented from across the continent and the African diaspora are Beauford Delaney, Ibrahim El-Salahi, Hoyt William Fuller, Wifredo Lam, Simone Leigh, Ernest Mancoba, Zanele Muholi, Kawira Mwirichia, Cauleen Smith, Alma Thomas, and George Albert Yon. Reflecting Pan-Africanism’s ideals of diversity and dialogue as well as its aspirations to egalitarianism, essays from more than a dozen scholars, artists, and practitioners speak to a range of themes and places, while discussing works in all media made or circulated outside the infrastructure of fine art, including LP albums, illustrated magazines, and manifestos"--
Published on the occasion of the exhibition of the same title, organized by the Art Institute of Chicago and MACBA Museo d'Arte Contemporaneo de Barcelona, in collaboration with KANAL-Centre Pompidou, the exhibition will be held at the Art Institute of Chicago (Dec. 15, 2024–Mar. 30, 2025), MACBA Museo d'Arte Contemporaneo de Barcelona (Nov. 6, 2025–Apr. 6, 2026), Barbican Centre, London (June 10–Sept. 26, 2026), and KANAL-Centre Pompidou, Brussels (Nov. 2026–Mar. 2027)
Keywords: Panafrikanismus; Kunst; Art, African / 20th century / Exhibitions; Pan-Africanism / Exhibitions; Ausstellungskatalog -- Art Institute of Chicago -- 2024-2025 -- Chicago, Ill.; Ausstellungskatalog -- Museu d'Art Contemporani de Barcelona -- 2025-2026 -- Barcelona; Ausstellungskatalog -- Barbican Centre -- 2026 -- London; Ausstellungskatalog -- Kanal Centre Pompidou -- 2026-2027 -- Brüssel